MRI in multiple sclerosis: an intra-individual, randomized and multicentric comparison of gadobutrol with gadoterate meglumine at 3 T - Saake, Marc; Langner, Soenke; Schwenke, Carsten; Weibart, Marina; Jansen, Olav; Hosten, Norbert; Dörfler, Arnd (European Radiology, 2016)
To compare contrast effects of gadobutrol with gadoterate meglumine for brain MRI in multiple sclerosis (MS) in a multicentre, randomized, prospective, intraindividual study at 3 T.Institutional review board approval was obtained. Patients with known or suspected active MS lesions were included. Two identical MRIs were performed using randomized contrast agent order. Four post-contrast T1 sequences were acquired (start time points 0, 3, 6 and 9 min). If no enhancing lesion was present in first MRI, second MRI was cancelled. Quantitative (number and signal intensity of enhancing lesions) and qualitative parameters (time points of first and all lesions enhancing; subjective preference regarding contrast enhancement and lesion delineation; global preference) were evaluated blinded.Seventy-four patients (male, 26; mean age, 35 years) were enrolled in three centres. In 45 patients enhancing lesions were found. Number of enhancing lesions increased over time for both contrast agents without significant difference (median 2 for both). Lesions signal intensity was significantly higher for gadobutrol (p < 0.05 at time points 3, 6 and 9 min). Subjective preference rating showed non-significant tendency in favour of gadobutrol.Both gadobutrol and gadoterate meglumine can be used for imaging of acute inflammatory MS lesions. However, gadobutrol generates higher lesion SI.o Contrast-enhanced MRI plays a key role in the management of multiple sclerosis. o Different gadolinium-based contrast agents are available. o Number of visibly enhancing lesions increases over time after contrast injection. o Gadobutrol and gadoterate meglumine do not differ in number of visible lesions. o Gadobutrol generates higher signal intensity than gadoterate meglumine.
EVALuna2:14582